2019
DOI: 10.2139/ssrn.3411137
|View full text |Cite
|
Sign up to set email alerts
|

Financing Conditions and Toxic Emissions

Abstract: Exploiting heterogeneity in U.S. firms' exposure to an unconventional monetary policy shock that reduced debt financing costs, I identify the impact of financing conditions on firms' toxic emissions. I find robust evidence that lower financing costs reduce toxic emissions and boost investments in emission reduction activities, especially capital-intensive pollution control activities. The effect is stronger for firms in noncompliance with environmental regulation. Examining the ability of regaining regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…This can stimulate enterprise vitality, increase R&D investment, and promote the improvement of green technology innovation level (Han, 2020). Goetz (2019) also confirmed that green credit can reduce the long-term debt financing cost of enterprises based on the data of American enterprises, thus promoting the green technology research and development of enterprises.…”
Section: Discussionmentioning
confidence: 80%
“…This can stimulate enterprise vitality, increase R&D investment, and promote the improvement of green technology innovation level (Han, 2020). Goetz (2019) also confirmed that green credit can reduce the long-term debt financing cost of enterprises based on the data of American enterprises, thus promoting the green technology research and development of enterprises.…”
Section: Discussionmentioning
confidence: 80%
“…In particular, Levine, Lin, Wang and Xie (2018) show how positive credit supply shocks in U.S. counties-due to fracking of shale oil in other countiesreduce local air pollution. In a similar vein, Goetz (2019) finds that financially constrained firms reduced toxic emissions when their capital cost decreased as a result of the U.S. Maturity Extension Program.…”
Section: Introductionmentioning
confidence: 87%
“…So, the short-term policy impact is stronger than the long-term one. Second, firms will gradually engage in green innovation, increase environmental expenditures, and seek to transform into an energy-saving, green, and low-carbon production model in the long run, so as to mitigate the policy impacts ( Goetz, 2019 ; He et al, 2019 ).…”
Section: Robustness Checksmentioning
confidence: 99%